Concept Design of Post-Mining River Naturalization with Nature Based Solution (NBS) Approach (Case Study: Sungai Daeng, West Bangka) - Mohammad Fardani Rizqullah; Diana Anggraeni; Irhamna Akbar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2022)
River naturalization is the restoration of river functions in a natural way. The application of river naturalization techniques is one of them by reforesting the river banks. The method of planting trees and reforestation is highly emphasized in this technique. This reforestation aims to absorb water on the ground surface into the soil to replenish groundwater reserves so that overflows do not occur. In the case of the Sungai Daeng researchers applied Nature-based solutions (NBS), which refers to the sustainable management and use of nature to overcome social and environmental challenges. As well as also applying river borders that function as a means of preserving river functions, with data from river cross-section measurements and river land ownership surveys which will later be processed into an idea in the form of discussion and how to apply and implement it, from the results of the discussion obtained land use for the application of design for the research area with a river length of ± 500 m, assuming the use of river border land ± 60 m for two sides, approximately 3000 m².